Analytical study on failure of national language policy's implementation in the Malaysian legal system / Khairul Naim Rafidi … [et al.] - Rafidi, Khairul Naim; Abu Kasim, Farahana Nabila; Anuar, Amiera Aimi; Wan Zawawi, Wan Nur Ain Nabilah (Faculty of Law, 2014)
Basically, this research project explains and studies on the failure of the national language policy's implementation in the Malaysian Legal System. It explores into the meaning of the national language, the position of the national language in Malaysia and several other countries, the relationship between the national language with Malaysia's history, legal jurisprudence, and psychology, together with the views from various perspectives, on the implementation of the national language in Malaysia. In this research, we have also read through landmark cases that reveal the importance of the national language, which the court has regrettably overlooked. There are several issues highlighted by the respondents in this research; which are crucial and must be brought to the attention of the public, legal officers, legal practitioners and academicians. Therefore, the research findings will create much needed awareness to the society about the importance of the national language in unifying the nation. In addition, a comparison is made of the situation in Malaysia and in other countries such as Indonesia, Singapore and Brunei. This will indirectly give some ideas, and help the relevant authorities to understand the reasons why the implementation of the national language in the Malaysian Legal System is vital in this country. At the same time, by conducting this research, we hope that it will be a guiding light, and grant to the injured parties, or the accused, in civil and criminal cases, the opportunity to seek justice, and ensure that justice is dispensed to all parties, regardless of their capability in conversing in either the English language or the national language. After collecting, analysing and justifying all the findings, based on the opinions and all the reliable facts and sources, we have come to a conclusion that it is possible to implement the national language in the Malaysian Legal System if the government, the Bar Council, the Attorney General's Chambers and the law firms in Malaysia, gives serious effort and attention, to overcome all the obstacles faced in the implementation, in order to implement the national language in this country.